1962
DOI: 10.1001/archneur.1962.04210030065009
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer's Neurofibrillary Changes

Abstract: of the central nervous system in a few con-ditions\p=m-\thecerebral cortex in Alzheimer's disease and the senile psychoses, and the substantia nigra and brain stem in parkinsonism.Recent observations of neurofibrillary changes in 2 fatal neurologic diseases occurring on the island of Guam, the parkinsonism-dementia complex (Hirano, Kurland, Krooth, and Lessell 1; Hirano, Malamud and Kurland 2) and the amyotrophic lateral sclerosis syndrome (Malamud, Hirano and Kurland3), revealed their quite remarkable numbers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
107
0
2

Year Published

1966
1966
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 398 publications
(116 citation statements)
references
References 30 publications
7
107
0
2
Order By: Relevance
“…1 Both the regional distribution of tau pathology in the brains of patients with AD and the sequential staging of its progression have been extensively described in postmortem studies. [2][3][4][5] These studies indicated, for the first time, that an early and relatively long preclinical phase of tau aggregation precedes the symptomatic stages of AD. 6,7 Despite this, the time course of tau pathology propagation, especially in relation to changes in the concomitant clinical and cognitive profiles of the individual patients, remains largely speculative because of the inherent limitations of post-mortem studies.…”
Section: Introductionmentioning
confidence: 85%
“…1 Both the regional distribution of tau pathology in the brains of patients with AD and the sequential staging of its progression have been extensively described in postmortem studies. [2][3][4][5] These studies indicated, for the first time, that an early and relatively long preclinical phase of tau aggregation precedes the symptomatic stages of AD. 6,7 Despite this, the time course of tau pathology propagation, especially in relation to changes in the concomitant clinical and cognitive profiles of the individual patients, remains largely speculative because of the inherent limitations of post-mortem studies.…”
Section: Introductionmentioning
confidence: 85%
“…In terms of neuropathological findings, it is characterized by the presence of numerous senile plaques and neurofibrillary tangles throughout the cerebral cortex (Hirano and Zimmerman, 1962; Kidd, 1964;Schoenberg et al, 1987;Yamaguchi et al, 1988;Wisniewski et al, 1989). The major protein in senile plaques has been identified as a 39-42 amino acid polypeptide referred to as the 3/A4 protein (Selkoe et al, 1986;Masters et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…In summarizing his quantitative and comparative anatomical data, Stephan (1975) clearly demonstrated the progressive increase of CA1, subicular, and entorhinal volumes in man. Interestingly, these archicortical and periarchicortical structures exhibit characteristic pathological cha~!ges in a variety of neurodegenerative diseases, including Alzheimer's disease (Hirano and Zimmerman 1962;McLardy 1970;Hooper and Vogel 1976;Kemper 1978;Hyman et al 1984;Braak and Braak 1991), Parkinson's disease (Braak and Braak 1990), Pick's disease (Jakob 1979), and Huntington's chorea (Bauer et al 1991 ;Braak and Braak 1992 a, b;Heinsen et al 1992), diseases which exclusively afflict man. Cytoarchitectonic studies of schizophrenia, an additional disease confined to the human brain, point to specific circumscribed neurodevelopmental disturbances in the entorhinal region (Jakob and Beckmann 1986;Arnold et al 1991;Beckmann and Jakob 1991).…”
Section: Introductionmentioning
confidence: 99%